GRANDI, Guilherme. Caminho como vocação: os paulistas e os transportes terrestres no centro-sul do Brasil. São Paulo: Annablume, 2024 - Nunes, Ivanil (História Econômica & História de Empresas, 2025)
The book “Path as a vocation: the paulistas and land transport in south-central Brazil”, published by Annablume, in 2024, is a synthesis of a long research path, followed by prof. Dr. Guilherme Grandi, from FEA/USP, whose starting point was duly based at Unesp, in Araraquara, at the end of the 1990s. For me, it is a personal pleasure to be able to draw some lines about this rich academic production because I have followed it since its inception. I soon feel like a witness and academically complicit in some of these reflections in this work presented; It can be said that the work analyzed here reflects the author's own academic-intellectual script over the last quarter of a century.